Alterations of Liver Functions and Morphology in a Rat Model of Prediabetes After a Short-term Treatment of a High-fat High-glucose and Low-dose Streptozotocin - Krisnamurti, Desak Gede Budi; Purwaningsih, Erni H.; Tarigan, Tri Juli Edi; Nugroho, Christian Marco Hadi; Soetikno, Vivian; Louisa, Melva (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The administration of high-fat and high-glucose in diet followed by a low-dose streptozotocin injection in rats could mimic hyperglycemia, prediabetic, or diabetic conditions in humans. However, whether the rat model may lead to early liver impairment was still unclear. AIM: This study was aimed to investigate the possible changes in liver functions and morphology in the rat model of prediabetes after a short-term administration of a high-fat and high-glucose diet followed by low-dose streptozotocin injection. METHODS: Eighteen male Wistar rats were divided into nine rats in the control group and nine in the prediabetic group. To induce prediabetic rats, high-fat high-glucose in daily diets for 3 weeks continued with once to twice low-dose streptozotocin was given. Rats in control groups were fed with a standard diet for 2 months. Afterward, we analyzed glucose control parameters, liver functions, and liver histology of the rats. RESULTS: High-fat, high-glucose diet combined with a low dose of streptozotocin successfully caused prediabetics in the rats. There was a significant increase in several liver enzymes, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), and gamma-glutamyl transferase (GGT). However, no significant changes were found in the serum lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) levels. The histological changes in the liver confirmed the increase in liver enzymes. CONCLUSION: Short-term administration of high-fat high-glucose in combination with low-dose streptozotocin triggers alterations in liver functions marker and liver morphology.